Spatial Inequality in Health Care Infrastructure in Allahabad District: A Geographical Study - Singh, Amit Kumar; Kumra, V. K. (National Geographical Journal of India, 2022)
Health is a fundamental human right and central to the concept of quality of life. Due to various socio-economic and political factors, there exists a widespread inequality in the distribution of health care facilities in India. The present study attempts to highlight the existing health care infrastructure and also tries to analyse the inter-block disparities regarding health care facilities in Allahabad district. To identify the regional disparities of health care infrastructure three broad categories have been identified i.e. availability of health care infrastructure, performance of public health care centres and accessibility to healthcare services. There is found considerable shortfall in the existing and required number of Primary Health Centres and manpower under the public health system in Allahabad district. Nearly 80 per cent of the total area of Allahabad district is suffering due to very poor health care infrastructure. Only four development blocks viz. Shankargarh, Phulpur, Chaka and Meja have relatively better health care facilities than the rest of the district. Analysis of block level disparities in health care infrastructures would help to identify specific deficiencies and suggest corrective measures to improve the healthcare system in the district for achieving the goal of ‘Health for all’. The state government needs to adopt viable policies and programmes and take some immediate actions to improve the health care infrastructure in Allahabad district.